PEMAHAMAN MENGENAI HAK DAN KEWAJIBAN PADA MATA PELAJARAN PKN MENGGUNAKAN METODE ROLE PLAYING PADA SISWA SEKOLAH DASAR DI KOTA TARAKAN - Atrisia Devina Mangalik; Nur Pangesti Apriliayana (Universitas Borneo Tarakan, 2024)
The aim of this research is to identify the application of material on rights and obligations for elementary school students as a good generation of the nation, so that learning is needed using effective and interesting ways and methods in the learning process. This research uses descriptive qualitative methods. Data collected was through literature reviews and questionnaires. The results of this research indicate that Citizenship Education Learning is considered boring for some students at Binalatung 045 State Elementary School. However, some of them also know the rights and obligations of PKn learning, but have not implemented them into their daily lives. The learning method that can be used is the role playing learning method so that elementary school students, especially SD Negeri 045 Binalatung, will be more enthusiastic about learning the rights and obligations in PKn subjects. Apart from that, the rights and obligations will be able to be implemented by future generations of the nation in accordance with the goals of the Indonesian State, namely to grow a young generation who live a democratic life in the nation and state.